Empedocles the Sorcerer and his Hexametrical Pharmaka. (2019) - Faraone, Christopher
Abstract: In one of his fragments, Empedocles addresses his protégé Pausanias, predicting or promising that he will learn pharmaka, a word that is usually understood to mean herbal 'drugs' or 'remedies' for disease, an interpretation that in turn seems to have been encouraged by a modern understanding that Empedocles was an empirically minded medical doctor. An alternate interpretation is suggested, however, by the recently published Getty Hexameters which use the word pharmaka several times to refer to hexametrical incantations that will protect a group of houses or a city from danger. These hexameters, moreover, are inscribed on a lead tablet of late-classical date that most probably came from the Sicilian city of Selinus, a date and a provenance that put its composition in close proximity to Empedocles himself.